ANALYZE THE VARIABILITY OF CONCRETE QUALITY IN THE WORK ON THE PROMENADE APARTMENT USING SPC (STATISTICAL PROCCES CONTROL) (Case Study: Queen City Mall Building Project, Hotel and Apartment Promenade) - Fauzi, Dwi Achmad; Alfafa, Jannah Rahmah; Suwandi, Putri Anggi Permata; Kristiawan, Agung (Science and Technology Research Centre, Universitas PGRI Semarang, 2024)
Abstract. Quality control in a job is very important because to know that a job is in accordance with quality standards and is carried out according to the schedule without delays in a project work. The research was conducted so that there was no repetition in a job on the Queen City Mall Building, Hotel and Promenade Apartment project. The method used in this study is the SPC (Statistical Process Control) method. Data collection was obtained from primary data in the form of concrete compressive strength data from the laboratory and secondary data in the form of RKS_STRUKTUR Atas_R0_11-12-2021. The results of the study showed that there were deviations in the quality of the concrete fc 25 MPa, 30 MPa, and 35 MPa which were under both lower and upper control without affecting the concrete quality standard.Â Keywords : Quality control, Statistical Process Control (SPC)